1997
DOI: 10.1074/jbc.272.30.18673
|View full text |Cite
|
Sign up to set email alerts
|

Identification of an 8-Lipoxygenase Pathway in Nervous Tissue of Aplysia californica

Abstract: Arachidonic acid is converted to (8R)-hydroperoxyeicosa-5,9,11,14-tetraenoic acid (8-HPETE) during incubations with homogenates of the central nervous system of the marine mollusc, Aplysia californica. 8-HPETE can be reduced to the corresponding hydroxy acid or be enzymatically converted to a newly identified metabolite, 8-ketoeicosa-5,9,11,14-tetraenoic acid (8-KETE). These metabolites were identified by high performance liquid chromatography, UV absorbance, and gas chromatography/mass spectrometry. Stereoche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 42 publications
0
13
0
Order By: Relevance
“…Lipids were extracted into ether and analyzed by reverse-phase HPLC as previously described (65). The 12-HETE was quantified by UV absorbance at 237 nm.…”
Section: Figurementioning
confidence: 99%
“…Lipids were extracted into ether and analyzed by reverse-phase HPLC as previously described (65). The 12-HETE was quantified by UV absorbance at 237 nm.…”
Section: Figurementioning
confidence: 99%
“…These enzymes oxygenate arachidonate in the 5R, 8R, 11R, or 12R configurations. The arachidonate (8R)-lipoxygenases have been studied in detail from two corals, Pseudoplexaura porosa and P. homomalla (46 -48), and from nervous tissue of Aplysia californica (43). Brash and co-workers (3) cloned and sequenced the (8R)-lipoxygenase from P. homomalla and found that it belonged to the lipoxygenase gene family.…”
Section: Different Strains Of Take-allmentioning
confidence: 99%
“…c Based on formation of 13-H(P)OTrE(n-3) only. (3,43,44). These enzymes oxygenate arachidonate in the 5R, 8R, 11R, or 12R configurations.…”
Section: Different Strains Of Take-allmentioning
confidence: 99%
“…Prior to analysis, samples were dried under a stream of nitrogen and reconstituted in ethyl acetate. Gas chromatography-mass spectrometry (GC-MS) analysis was performed as described previously (53), using a Hewlett Packard 5987A GC-MS instrument equipped with a DB-1 fused-silica capillary column (30 m by 0.2 mm), using helium as a carrier gas at injector and source temperatures of 220°C and 200°C, respectively. Samples were ionized by electron impact (70 eV).…”
mentioning
confidence: 99%